Induction of potent antitumor immunity by intradermal DNA injection using a novel needle‐free pyro‐drive jet injector. Issue 1 (17th October 2022) - Inoue, Shinya; Mizoguchi, Izuru; Sonoda, Jukito; Sakamoto, Eri; Katahira, Yasuhiro; Hasegawa, Hideaki; Watanabe, Aruma; Furusaka, Yuma; Xu, Mingli; Yoneto, Toshihiko; Sakaguchi, Naoki; Terai, Kazuhiro; et al.
Abstract: The current success of mRNA vaccines against COVID‐19 has highlighted the effectiveness of mRNA and DNA vaccinations. Recently, we demonstrated that a novel needle‐free pyro‐drive jet injector (PJI) effectively delivers plasmid DNA into the skin, resulting in protein expression higher than that achieved with a needle syringe. Here, we used ovalbumin (OVA) as a model antigen to investigate the potential of the PJI for vaccination against cancers. Intradermal injection of OVA‐expression plasmid DNA into mice using the PJI, but not a needle syringe, rapidly and greatly augmented OVA‐specific CD8 + T‐cell expansion in lymph node cells. Increased mRNA expression of both interferon‐γ and interleukin‐4 and an enhanced proliferative response of OVA‐specific CD8 + T cells, with fewer CD4 + T cells, were also observed. OVA‐specific in vivo killing of the target cells and OVA‐specific antibody production of both the IgG2a and IgG1 antibody subclasses were greatly augmented. Intradermal injection of OVA‐expression plasmid DNA using the PJI showed stronger prophylactic and therapeutic effects against the progression of transplantable OVA‐expressing E.G7‐OVA tumor cells. Even compared with the most frequently used adjuvants, complete Freund's adjuvant and aluminum hydroxide with OVA protein, intradermal injection of OVA‐expression plasmid DNA using the PJI showed a stronger CTL‐dependent prophylactic effect. These results suggest that the novel needle‐free PJI is a promising tool for DNA vaccination, inducing both a prophylactic and a therapeutic effect against cancers, because of prompt and strong generation of OVA‐specific CTLs and subsequently enhanced production of both the IgG2a and IgG1 antibody subclasses. Abstract : The intradermal vaccination with OVA‐expression plasmid DNA using the PJI, but not a needle syringe, induces a strong antitumor immune response via enhanced generation of antigen‐specific CTLs, with subsequent killing of the target cells, and that efficient antigen‐specific antibody production is also enhanced. Notably, induction of prophylactic antitumor immunity was faster and stronger with the injection of OVA‐expression plasmid DNA using the PJI than with the injection of OVA protein combined with alum or complete Freund's adjuvant.